Study of Renal Morphological Changes After Extracorporeal Shock Wave Lithotripsy (Eswl) (Journal of Chittagong Medical College Teachers' Association, 2018)
Background: To find out the renal morphological changes after Extracorporeal Shock Wave Lithotripsy (ESWL) both in short and long term. Materials and methods: This prospective study was carried out in the in the Department of Urology, Chittagong Medical College Hospital, Chittagong from January 2009 to January 2010. Patients with symptom, radio logically proved renal stone(s) measuring less than 2 cm in diameter and who are normotensive were enrolled in this study. Results: All 50 patients were divided into four age groups. The age ranged from 38 to 68 years and the maximum number was found in the age group of 51-60 years. The mean age was 50.9 years with Standard Deviation (SD)±11.2 years. Out of which 58.0% were male and rest 42.0% were female patients. All patients had normal morphological kidney ESWL but after ESWL 4(8.0%) had peri renal hematoma hydronephrosis / increased size of the kidney. The difference was not statistically significant (p>0.05) before and after ESWL. Sub capsular hematoma or peri renal hematoma, hydronephrosis of kidney and increased size of the kidney diagnosed by USG of KUB region and CT scan. All patients had normal kidney before ESWL but after ESWL 6(12.0%) had paren chymal scarring / decreased size of the kidney. The difference was statistically significant (p0.05) before and after ESWL. Conclusion: ESWL is a good option for the management of renal stone less than 2cm. ESWL is considered a safe and well-tolerated procedure. Serious complications are rare, but need to be considered in certain number of patients with complications at short and long term after ESWL. Transient renal morphological changes occurs within short time and at variable period after ESWL.Post ESWL complication’s like renal morphological changes are rare, which become normal with in variable period.JCMCTA 2017 ; 28 (2) : 94-98